Monster blood - Stine, R. L. (New York : Scholastic, 1992)
Soon after he purchases a dusty can of monster blood at the funky old toy store near his great-aunt's house, Evan begins to notice some strange things happening to the people around him.
640
Accelerated Reader AR
Keywords: Supernatural -- Fiction